An effective mosquito-repellent topical product from liquid crystal-based tea tree oil - Fonseca-Santos, Bruno [UNESP]; Del Nero Pacheco, Camila [UNESP]; Pinto, Mara Cristina [UNESP]; Chorilli, Marlus [UNESP] (Elsevier, 2019)
Diseases such as dengue, malaria, yellow fever and others transmitted by culicides determine high rates of morbidity and mortality, especially in tropical countries. An alternative to avoid bites is the use of repellents. The most commonly used is DEET (N, N-diethyl-3-m-toluamide) repellent, but there are reports describing cases of toxicity with misuse or long-term use. Due to these disadvantages many people prefer to use natural products for repellents purposes. Studies have shown that different essential oils have repellent activity, but research should be conducted in order to obtain formulations that are effective in fixing aromatic compounds on the skin and increasing the duration of repellency. Nanostructured systems for the incorporation of natural active principles, such as liquid-crystalline systems (LCS), have advantages in solubilization of compounds, increase stability and effectiveness of them. Four formulations composed of water, hydrogenated castor oil PEG-40, as surfactant, and melaleuca essential oil, as oily phase, were prepared and characterized by polarized light microscopy, rheological, mechanical and bioadhesive behavior. Their in vivo repellent activity against the Aedes aegypti mosquitoes was determined. Presence of cubic liquid-crystalline mesophase regions and microemulsions were confirmed by polarized microscopy. The rheology tests showed that the fluids are non-Newtonian like pseudoplastics fluid and they have elastic characteristics. The bioadhesion assay showed that the cubic mesophase formulations are more bioadhesive than the microemulsions. Formulations showed repellency against A. aegypti. The results show the repellent activity of nanoestructured systems based on essential oil of melaleuca and prospects for the development of new and innovative formulations based natural products.
Keywords: Aedes aegypti; Bioadhesion; Cubic phase; Repellency; Skin; Surfactant